Slow Down in Demand Affects Corporate Growth - An Empirical Study - Baral, S.K. (Journal of Research in Marketing (ISSN: 2292-9355), 2013)
Growth of Indian market continued to slow down in 2012-13, but could witness a slow-paced recovery later this year, contingent on improved governance and concerted action to resolve structural bottlenecks. Unresponsive business and consumer confidence, reflected in various surveys, is expected to drag growth down. Rising prices and slowing growth are making Indians check their household shopping list from soaps, shampoos and skincare to packaged groceries, food items, electronics products, medicines etc. This financial year, India Inc would face several stress factors, the most significant being a slowdown in demand. One in four companies would see a demand slowdown, while two out of every three sectors of the economy would record lower revenue growth, according to CRISIL’s ‘State of the Nation’ report, released on 17th December 2013. This paper highlights some important aspects in context to the issues and challenges faced by the Indian Corporate during slowdown in demand.